Innovative technologies and educational quality: insights from Mongolia and Kazakhstan - Kabassova, Kanziya; Nyamsuren, Khosbayar; Miller, Antony D.; Piven, Iurii; Kravtsov, Yuriy (International Journal of Evaluation and Research in Education (IJERE), 2025)
The study explores the digital potential and prospects of advanced innovative technologies in higher education institutions, compared to global practices. The research is situated within the theoretical framework of socio-constructivist learning theory, emphasizing the role of digital technologies in facilitating collaborative learning environments. Findings indicate that digitalization and inclusive educational practices are evolving into central elements of educational strategies. This study highlighted specific case studies, such as the implementation of virtual reality and e-learning platforms at Otgontenger University, demonstrating their significant impact on enhancing student engagement and learning outcomes.